Feasibility and importance of an automatic controller for solar hot water system - Hasan, Mohammed A.; Rahman, Arifur K M Zillur; Azad, AKM Abdul Malek (© 2011 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 2011 IEEE Global Humanitarian Technology Conference, GHTC 2011; Seattle, WA; United States; 30 October 2011 through 1 November 2011 [© 2011 Institute of Electrical and Electronics Engineers Inc.] The conference paper's definite version is available at: http://doi.org/10.1109/GHTC.2011.36